1988
DOI: 10.1016/s0886-3350(88)80142-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the need for secondary capsulotomy during a five-year follow-up

Abstract: From 783 consecutive extracapsular cataract extractions with intact posterior capsules at the close of surgery, 655 eyes were available for examination three years after surgery and 447 eyes were available five years after surgery. By five years postoperatively, the need for secondary capsulotomy was 49% of 67 eyes that had not received an implant, 23% of 159 eyes that had received a Binkhorst iridocapsular lens, and 13% of 221 eyes that had received a posterior chamber lens. Among posterior chamber lenses, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In Percival & Setty's (1988) study the incidence of capsulotomy for 3 years of follow-up varied from 4.7% for eyes with implanted PCL's to 40% for eyes without implants. We found a total need for capsulotomy of 24%.…”
Section: Discussionmentioning
confidence: 94%
“…In Percival & Setty's (1988) study the incidence of capsulotomy for 3 years of follow-up varied from 4.7% for eyes with implanted PCL's to 40% for eyes without implants. We found a total need for capsulotomy of 24%.…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Percival & Setty (1988), it was found that extracapsular cataract extraction led to a YAG capsulotomy by five years in 49% of the eyes without lens implant, in 23% of eyes with a Binkhorst iridocapsular lens, and in 13% of eyes that had received a posterior chamber lens. The surface area of the posterior chamber lens was considered to be an important factor in inhibiting capsule opacification.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior capsule opacification (PCO) is one of the most common complications of cataract extraction with intraocular lens (IOL) implantation, occurring in 36% to 97% of cases in the first 2-4 years after extracapsular cataract surgery [1][2][3][4][5][6] . Since the PCO usually develops over years and leads to a slow decrease in visual acuity (VA), progression over time is the important factor in PCO evaluation 7 .…”
Section: Introductionmentioning
confidence: 99%